Pathophysiology of Green Teeth due to Hyperbilirubinemia: A Literature Review - Kusumawardani, Anisa; Ardini, Yunita Dewi; Hasan, Taufiq Hidayat; Amat, Nur Araziemah (2021)
This poster revealed a literature review regarding the pathophysiology of green teeth due to hyperbilirubinemia. This study was presented at the 28th International Association of Paediatric Dentistry [IAPD] Congress 10-13 June 2021